Overview of Women's Reproductive Health Problems among Foreign Tourists in Health Services in Bali - Anak Agung Ngurah Surya Wira Mahotama Putra; Putu Indah Budi Apsari; I Made Pariartha (Indonesian Socety of Obstetrics and Gynecology, 2026)
Objectives: To understand the overview of women's reproductive health problems among foreign tourists in several health services in Bali in 2022-2023. Methods: The research design used is descriptive research with a cross-sectional method. The study sample consists of 103 samples selected through purposive sampling. Data from the research results will be analyzed univariately and processed using SPSS version 27. The research locations to be used are two private hospital in Bali Results: The research results on foreign tourists with women's reproductive health problems revealed that the age group was predominantly 20-35 years, with 31 (60.8%) in 2022 and 34 (65.4%) in 2023. Most foreign tourists who visited did not have insurance, amounting to 32 (62.7%) in 2022 and 36 (69.2%) in 2023. The most common diagnosis was prolonged labor, with 20 (39.2%) in 2022 and 11 (21.2%) in 2023. The most frequent complaint was abdominal pain, experienced by 30 (58.8%) in 2022 and 19 (36.5%) in 2023. For the treatment of foreign patients with reproductive health issues, non-pharmacological treatment was predominant, with 34 (66.7%) in 2022 and 31 (59.6%) in 2023. Conclusion: Based on the research conducted, the overview of women's reproductive health problems among foreign tourists in several health services in Bali in 2022-2023 is dominated by the age group 20-35 years, most of whom have health insurance. The most common diagnosis is prolonged labor, with the majority experiencing complaints of lower abdominal pain, and treatment predominantly involving non-pharmacological methods.